Acceptability of strata title in Brunei Darussalam: an integrated solution to sustainable living - Omar, Mohd Don; Ali, Qaisar (Frontiers in Built Environment, 2023)
The recent traction in strata title living (STL) has addressed legal, regulatory, and governance issues to a certain extent. Despite addressing these underlying issues, the acceptance of STL remains low in Brunei Darussalam due to the low understanding of the features shaping residents’ perceptions and expectations. Accordingly, this study aims to explore the features of STL and examine how they contribute to enhancing the acceptance of STL (ASTL). Considering STL as an innovative living arrangement, we employ the diffusion of innovation (DOI) theory to categorize the factors affecting 201 Bruneian residents’ perceptions of ASTL. The findings reveal that perceptions of resource facilitation, relative advantages, and compatibility features of STL have the highest effect on ASTL. Whereas, perceptions of trialability, complexity, and observability have the lowest effect on ASTL. This study contributes to developing commercialization strategies for ST properties by understanding the features affecting the perceptions of ST residents.